The Social Construction of Family Roles in Migrant Worker Income Management to Build Family Economy - Tutik Sulistyowati; Wahyudi Wahyudi; Salahudin Salahudin; IRADHAD TAQWA SIHIDI (Jurnal Studi Pemerintahan, 2022)
This paper aims to explain the social construction of family roles in migrant workers’ income management. Many migrant worker families are unable to manage their income correctly. This social construction would affect the community by giving negative stigma to the families of migrant workers. This research was conducted using a descriptive method with a qualitative approach. The subjects were selected based on proportional sampling, namely people who live close to the families of migrant workers, extended families of migrant workers, and community leaders. The results of this study indicate that, in reality, some couples of migrant worker families can manage their income well, resulting in the income of migrant workers that does not have a meaningful impact on the family. The findings of this study contribute to developing a theory of social construction, where reality is the result of personal understanding, which is used as a shared understanding in the community. This shared understanding gives a new stigma to the reality of migrant worker families. The research limitation is that the data used are only obtained from subject interview data and case observations in the field, so the research findings limitedly describe the study of social construction in general. Future research that can be conducted based on this finding is investigating the effect of poor income management on the increasing migrant workers’ family disharmony.